Music versus midazolam to alleviate anxiety and physiological responses in patients receiving spinal anesthesia: A prospective randomized controlled study - Sucher, Siwalai; Yubonman, Rachata; Nonphiaraj, Saranyoo; Ruenhunsa, Thitinuch; Kittiponghansa, Apinya; Chujai, Pornsuk (Asia-Pacific Journal of Science and Technology, 2025)
This study aimed to evaluate the anxiety levels and physiological responses between music listening and given intravenous midazolam for perioperative anxiolytics in patients who receiving spinal anesthesia (SA). This prospective, randomized, controlled trial was conducted in adult patients undergoing elective surgery under SA. Participants were randomly assigned to either the music group (Mu group) or the midazolam group (Mi group). The Mu group listened to their preferred music, while the Mi group received an intravenous midazolam. Anxiety levels were assessed using State-Trait Anxiety Inventory (STAI) questionnaire, and physiological parameters were recorded pre- and postoperatively. The primary outcome was the change in STAI score from pre- to postoperative assessment. Secondary outcomes included the changes of physiological parameters, incidence of complications, and patient satisfaction. A total of 72 patients completed the study, 38 patients in Mu group and 34 patients in Mi group. The mean change in STAI score was -2.9 (SD 8.0) in the Mu group and -5.7 (SD 6.6) in the Mi group, with a mean difference of 2.78 (95% CI -0.7 to 6.3, p = 0.114). There were no significant differences in physiological parameters or complication rate between groups. Patient’s satisfaction scores were high in both groups. These finding suggest that music may be a viable alternative to midazolam for intraoperative anxiolysis in patients undergoing SA.